2022
DOI: 10.1093/eurheartj/ehac544.1867
|View full text |Cite
|
Sign up to set email alerts
|

Chronic thromboembolic pulmonary hypertension global cross-sectional scientific survey (CLARITY) – interim results on the adoption and perception of guidelines

Abstract: Background The chronic thromboembolic pulmonary hypertension (CTEPH) global cross-sectional scientific survey (CLARITY) was established to provide insights into current clinical practices and unmet needs in the diagnosis and treatment of CTEPH. The European Society of Cardiology (ESC) plays a leading role in establishing guidelines (GLs) for clinical decision-making in acute pulmonary embolism (PE) and CTEPH. It is of interest to better understand how these GLs affect real-world practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The CLARITY survey found that the most frequent barriers affecting the detection of CTEPH after PE reported by respondents (353 physicians from Europe, Asia–Pacific and the Americas) were low disease awareness among nonexperts (77%), lack of structured follow-up after acute PE (56%), nonspecific presentation of disease (43%), incomplete understanding of the natural history of disease (39%) and lack of clinical guidelines to screen for possible CTEPH (73, 23%) [ 25 ]. Moreover, low adherence to guidelines was reported as a barrier to CTEPH diagnosis by approximately one-third of respondents [ 26 ]. The variability in the physicians’ practices, as shown in this survey, could support this finding that more comprehensive guidelines on PE follow-up are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The CLARITY survey found that the most frequent barriers affecting the detection of CTEPH after PE reported by respondents (353 physicians from Europe, Asia–Pacific and the Americas) were low disease awareness among nonexperts (77%), lack of structured follow-up after acute PE (56%), nonspecific presentation of disease (43%), incomplete understanding of the natural history of disease (39%) and lack of clinical guidelines to screen for possible CTEPH (73, 23%) [ 25 ]. Moreover, low adherence to guidelines was reported as a barrier to CTEPH diagnosis by approximately one-third of respondents [ 26 ]. The variability in the physicians’ practices, as shown in this survey, could support this finding that more comprehensive guidelines on PE follow-up are needed.…”
Section: Discussionmentioning
confidence: 99%